Real-life monsters : a psychological examination of the serial murderer - Giannangelo, Stephen J. (Santa Barbara, Calif. : Praeger, 2012)
Examines serial murder and the bases for these crimes, and explores eight case studies of murderers.
Part 1. Development of a serial murderer -- Introduction: an identification of the offender -- Clinical diagnoses and serial killer traits -- Biology and its effect on violent behavior -- Environment, background, and personality -- Part 2. Toward an examination of a theory of violence -- Theoretical discussion and methodology -- Case studies: Andrei Chikatilo, Arthur Shawcross, Jeffrey Dahmer, Edmund Kemper, Anthony Sowell, Aileen Wuornos, Dennis Rader, Rodney Alcala -- Reflecting on case studies -- Theoretical analysis and development -- Conversation with a monster?
Includes bibliographical references (pages 173-184) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Serial murderers -- Psychology; Criminal psychology; Homicide -- psychology; Criminal Psychology; Tueurs en série -- Psychologie; Psychologie criminelle; Criminal or forensic psychology; MEDICAL -- Mental Health; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; PSYCHOLOGY -- Psychopathology -- General; Serial murderers -- Psychology; dissertations; Case studies; Academic theses; Thèses et écrits académiques.